VARIASI BAHASA; SLANG DAN JARGON TUKANG OJEK DI PANGKALAN OJEK JALAN OSCAR RAYA BAMBU APUS PAMULANG TANGERANG SELATAN BANTEN - Hendra Sastratmaja (Institut Agama Islam Negeri Palopo, 2013)
Essentially language is a communication tool which includes the interactional parts by people. In interaction, people in particular groups usually use informal spoken language rather than formal language. They usually use this informal language because they know well each other. Slang and jargon become a special language for particular groups of people. Through this paper, the writer will explain the using of slang and jargon the ojek drivers in Bambu Apus Pamulang Tangerang Selatan Banten